2022
DOI: 10.1111/cid.13122
|View full text |Cite
|
Sign up to set email alerts
|

Early marginal bone loss around dental implants to define success in implant dentistry: A retrospective study

Abstract: Purpose The aim of this study was to establish an objective criterion in terms of marginal bone level (MBL) to know the prognosis of an implant. Materials and Methods A group of 176 patients in whom 590 implants were placed were included in this retrospective study. Patients older than 18 years, presenting either Kennedy class I or II edentulous section, or totally edentulous at least in one of the dental arches were included in this study. Those with any type of disturbance able to alter bone metabolism or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 89 publications
2
37
0
Order By: Relevance
“…In fact, it has been shown that if initial marginal bone loss exceeds 0.5 mm over the first 6 months, it is very likely that the loss will extend to 2 mm after 2 years, increasing the risk for the occurrence and progression of peri-implantitis. 55 A 10-year prospective study validated that implants that exceed 0.5 mm during the first year of function are 5.43 times more prone for future periimplantitis development. 56 In relation to these observations, it has been speculated that the partial exposure of implant surface to the peri-implant sulcus can facilitate bacterial colonization, which may increase the risk for inflammatory disease.…”
Section: Sth and Peri-implant Healthmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, it has been shown that if initial marginal bone loss exceeds 0.5 mm over the first 6 months, it is very likely that the loss will extend to 2 mm after 2 years, increasing the risk for the occurrence and progression of peri-implantitis. 55 A 10-year prospective study validated that implants that exceed 0.5 mm during the first year of function are 5.43 times more prone for future periimplantitis development. 56 In relation to these observations, it has been speculated that the partial exposure of implant surface to the peri-implant sulcus can facilitate bacterial colonization, which may increase the risk for inflammatory disease.…”
Section: Sth and Peri-implant Healthmentioning
confidence: 96%
“…Although there is no conclusive clinical evidence indicating that there is a direct link between a certain threshold of STH and an increased risk for the development of peri‐implant diseases, early marginal bone loss, although often self‐limiting, may jeopardize long‐term health. In fact, it has been shown that if initial marginal bone loss exceeds ~0.5 mm over the first 6 months, it is very likely that the loss will extend to 2 mm after 2 years, increasing the risk for the occurrence and progression of peri‐implantitis 55 . A 10‐year prospective study validated that implants that exceed 0.5 mm during the first year of function are 5.43 times more prone for future peri‐implantitis development 56 .…”
Section: Significance Of Sth On Peri‐implant Health and Estheticsmentioning
confidence: 99%
“…Bone loss associated with dental implants is one of the most studied and experimented with topics in implant dentistry. It has been widely debated and researched across the globe for decades still one has formulated a concrete statement or concept [15][16][17]. Recently many pioneer researchers, including Young et al, studied variants of CBCT and its role in dental implantology, and they claimed that CBCT is an ideal radiographic tool for estimating alveolar bone losses [18].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, EMBL up to 1.5–2 mm followed by a maximum of 0.2 mm annually thereafter, was commonly observed and considered a defining criterion of implant success 21–23 . The definition of success in implant dentistry has evolved in recent years and EMBL <0.5 mm is currently accepted as a threshold between peri‐implant bone physiological stability and a borderline condition potentially favoring subsequent peri‐implant pathology 24–29 . EMBL may lead to unwanted treated implant surface exposure to the oral cavity microbiome and surface roughness facilitates bacterial biofilm adhesion, maturation, and colonization.…”
Section: Introductionmentioning
confidence: 99%